A systematic review, meta‐analysis and meta‐regression of the global prevalence of Toxoplasma gondii infection in wild marine mammals and associations with epidemiological variables. Issue 5 (16th March 2022) - Li, Man‐Yao; Gao, Xiao‐Nan; Ma, Jun‐Yang; Elsheikha, Hany M.; Cong, Wei
Abstract: Toxoplasma gondii infection in wild marine mammals is a growing problem and is associated with adverse impacts on marine animal and public health. This systematic review, meta‐analysis and meta‐regression estimates the global prevalence of T. gondii infection in wild marine mammals and analyses the association between T. gondii infection and epidemiological variables. PubMed, Web of Science, Science Direct, China National Knowledge Infrastructure, and Wanfang Data databases were searched until 30 May 2021. Eighty‐four studies ( n = 14, 931 wild marine mammals from 15 families) were identified from literature. The overall pooled prevalence of T. gondii infection was 22.44% [3848/14, 931; 95% confidence interval (CI): 17.29–28.04]. The prevalence in adult animals 21.88% (798/3119; 95% CI: 13.40–31.59) was higher than in the younger age groups. North America had a higher prevalence 29.92% (2756/9243; 95% CI: 21.77–38.77) compared with other continents. At the country level, the highest prevalence was found in Spain 44.26% (19/88; 95%CI: 5.21–88.54). Regarding climatic variables, the highest prevalence was found in areas with a mean annual temperature >20°C 36.28% (171/562; 95% CI: 6.36–73.61) and areas with an annual precipitation > 800 mm 26.92% (1341/5042; 95% CI: 18.20–36.59). The subgroup and meta‐regression analyses showed that study‐level covariates, including age, country, continent, and mean temperature, partly explained the between‐study heterogeneity. Further studies are needed to investigate the source of terrestrial to aquatic dissemination of T. gondii oocysts, the fate of this parasite in marine habitat and its effects on wild marine mammals.